2014
DOI: 10.3109/17453674.2014.925351
|View full text |Cite
|
Sign up to set email alerts
|

10-year results of the uncemented Allofit press-fit cup in young patients

Abstract: Background and purposeUncemented acetabular components in primary total hip arthroplasty (THA) are commonly used today, but few studies have evaluated their survival into the second decade in young and active patients. We report on a minimum 10-year follow-up of an uncemented press-fit acetabular component that is still in clinical use.MethodsWe examined the clinical and radiographic results of our first 121 consecutive cementless THAs using a cementless, grit-blasted, non-porous, titanium alloy press-fit cup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
3
25
1
Order By: Relevance
“…However, prediction of longterm implant performance is difficult and definitive results regarding aseptic loosening are available only after lengthy followup [24,32,33]. Widespread use of poor-performing implants might occur before these results are available [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, prediction of longterm implant performance is difficult and definitive results regarding aseptic loosening are available only after lengthy followup [24,32,33]. Widespread use of poor-performing implants might occur before these results are available [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…After its re-introduction in the 1990s, the resurfacing prosthesis became quite popular, especially for use in the younger patient, and this could have impacted the number of cohorts of younger patients receiving THA. An additional explanation for our findings could be that collecting data such as primary-and subsequent revision arthroplasty outcomes requires strict and intensive follow-up of young patients, as also suggested by others (8)(9)(10)(11). As revisions are often performed in specialised referral centres, practice can lead to mixed cohorts, or a number of patients lost to follow-up.…”
Section: Possible Explanationsmentioning
confidence: 68%
“…Other authors have reported a high rate of revision due to problems occurring at the liner-metal shell couple21,22). Similar observations are echoed in reports from other national joint registries232425). Hence, questions prevail on whether uncemented acetabular components in primary THRs are the panacea for long-term survival in young and active patients.…”
Section: Introductionmentioning
confidence: 82%